2015
DOI: 10.4274/mjima.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

Point Prevalence of Hospital-Acquired Infections in Ege University Hospital

Abstract: Giriş:Hastane kökenli ya da sağlık bakımı ile ilişkili enfeksiyonların (HE) görülme sıklığı ülkeden ülkeye, hatta aynı hastanenin farklı birimlerine göre değişebilmektedir. Prevalans çalışmaları ile hastanelerdeki enfeksiyon sorunu daha geniş bir perspektifte tüm hastaneyi kapsayacak şekilde ortaya konulabilir ve kontrol önlemleri bu kapsamda değerlendirilebilir. Bu çalışmada bir üçüncü basamqk eğitim hastanesi olan hastanemizde 23 Aralık 2013 tarihinde yatan hastalardaki HE prevalansı irdelenmiştir. Gereç ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Although HCAM is a relatively small part of healthcareassociated infections (34), it may result in severe consequences such as significant morbidity and mortality. Durand et al (4) reported that HCAM accounted for 40% of 495 acute bacterial meningitis episodes in a 27-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Although HCAM is a relatively small part of healthcareassociated infections (34), it may result in severe consequences such as significant morbidity and mortality. Durand et al (4) reported that HCAM accounted for 40% of 495 acute bacterial meningitis episodes in a 27-year period.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkiye, the HAI rate is generally reported to be between 1% and 16.5%, and in ICUs, it ranges from 5.3% to 65.3%. [13][14][15][16] Based on these studies, the HAI rate in our research (5.5%) is comparatively low. This variation could be attributed to differences in hospital bed capacities, the types of patients, distinct risk factors, and the non-inclusion of certain departments where HAIs are more prevalent, such as hematology, oncology, and transplantation, in our study.…”
Section: Discussionmentioning
confidence: 84%
“…According to the literature, the prevalence of NIs in ICU ranges from 7.2% to 51%. (7,(13)(14)(15). Ventilator-associated pneumonia (VAP), urinary system infection, blood infection-related to the catheter, and surgical site infections (SSI) are reported as the most common NIs (3,13,16).…”
Section: Introductionmentioning
confidence: 99%
“…(7,(13)(14)(15). Ventilator-associated pneumonia (VAP), urinary system infection, blood infection-related to the catheter, and surgical site infections (SSI) are reported as the most common NIs (3,13,16). Knowledge of transmission routes of NIs and taking necessary precautions are of crucial importance to prevent NIs (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation